Maximal exponent of the Lorentz cones - Aubrun, Guillaume; Bai, Jing (Comptes Rendus. Mathématique)
We show that the maximal exponent (i.e., the minimum number of iterations required for a primitive map to become strictly positive) of the $n$-dimensional Lorentz cone is equal to $n$. As a byproduct, we show that the optimal exponent in the quantum Wielandt inequality for qubit channels is equal to $3$.